First women : the grace and power of America's modern First Ladies - Brower, Kate Andersen (Harper, an imprint of HarperCollinsPublishers, 2016)
"From the #1 New York Times bestselling author of the groundbreaking backstairs look at the White House, The Residence, comes an intimate, news-making look at the true modern power brokers at 1600 Pennsylvania Avenue: the First Ladies, from Jackie Kennedy to Michelle Obama,"--Amazon.com.